The Defense of Poland and its risks as the foundation of the national defense - Górska-Rożej, Karina (Management and Administration Journal, 2023)
The changing nature of threats poses Poland with the task of expanding its Defense System. Prior to joining NATO Polish defense was recognized only for military threats, while the effects of change in the twenty-first century need to take into account non-military threats. Today an elaborated definition of defense states that this is an area of national security including integratedopposing political threats -the military using - military and civilian - State resources, and organized defense system. Therefore the catalogue of risks was expanded for the whole Defense System of Poland, which was presented in the article.